Analisis Efektifitas Iklan Video Pada Studio recording Dottore Menggunakan Pengukuran EPIC Model - Supardianto, Supardianto (Politeknik Negeri Batam, 2023)
Video advertisements play a crucial role in promoting services and enhancing the brand awareness of a business, including Dottore Recording Studio. This research aims to analyze the effectiveness of the video advertisements utilized by Dottore in influencing its audience. The development method employed is the Villamil-Mollina design, using the EPIC model as its measurement tool. The examined advertisement video has a duration of 48 seconds and focuses on presenting Dottore Recording Studio as a solution to audio recording challenges. The EPIC rate measurement for this advertisement showed a result of 4.09, indicating its effectiveness, suggesting that the ad successfully achieved its communication objectives and effectively influenced the audience. Analysis using the EPIC model revealed that Dottore's video advertisement managed to capture the audience's attention and interest (empathy), convince them to consider and utilize Dottore Recording Studio's services (persuasion), create a strong impression on the audience (impact), and convey the message clearly and efficiently (communication). These findings affirm that video advertisements with a visual storytelling approach and creative content can be an effective instrument in achieving marketing targets and strengthening brand awareness. The results of this study provide insights and recommendations for Dottore to continuously optimize the use of video advertisements in its marketing strategy.